KKN Tematik: Sinergi Pemberdayaan Masyarakat Berbasis Kesehatan, Lingkungan, dan Sosial Agama di RW 2 Kalurahan Pandeyan - Permatasari, Cahyaning Kilang; Kumalasari, Nuria Putri; Aida Yuliana, Mia Noor; Arief Hidayat, Asharudin; Akram, Akmalul; Rukmana, Dimas Nurfianto; Alroy, Muhammad; Setyawan, Dwi Okka; Lisanto, Riefath Fajar; Supodo, Agustinus; Dwiyatno, Eko (Gemi: Jurnal Penelitian dan Pengabdian, 2025)
Community empowerment aims to increase public participation in meeting their needs and solving problems. This was carried out through the 2025 Thematic Community Service Program (KKN) in RW 02, Pandeyan Subdistrict, Umbulharjo, Yogyakarta, involving by a Field Academic Advisor, 10 students and 11 work programs focused on health, environment, and socio-religious sectors. The service methods included education, public services, facility provision, and group mentoring. Results showed a positive response from residents with active participation in various activities such as free health checks, elderly exercise programs, waste sorting, community clean-ups, and tutoring sessions. This program is expected to raise awareness of health, environmental management, and religious-social values while strengthening community solidarity.